Praise of Prof Lorenzo Mérola (1880 - 1935) - Lamas Pouey, E (Cirugía del Uruguay, 2020)
On the occasion of the second anniversary of the death of Prof. Mérola, the Society of Surgery of Montevideo resolved to adhere to the tribute that in his memory was paid by friends and disciples of the eminent Master whose premature disappearance deprived our surgical school of one of his most brilliant animators